Metabolic Energy Contributions During High-Intensity Hatha Yoga and Physiological Comparisons Between Active and Passive (Savasana) Recovery - Lee, Kwang-Ho; Ju, Hyo-Myeong; Yang, Woo-Hwi (Frontiers in Physiology, 2021)
Purpose: To investigate metabolic energy contributions during high-intensity hatha yoga (HIHY) and to compare changes in physiological variables between active and passive recovery methods. Methods: Twenty female yoga instructors (n = 20) performed 10 min of HIHY (vigorous sun salutation). Upon completion, they were randomly assigned to either active (walking; n = 10) or passive (savasana; n = 10) recovery groups, for a period of 10 minutes. During HIHY, physiological variables such as heart rate (HRpeak and HRmean), oxygen uptake (VO2peak and VO2mean), and blood lactate concentrations (peak La−) were measured. Energetic contributions (phosphagen; WPCR, glycolytic; WGly, and oxidative; WOxi) in kJ and % were estimated using VO2 and La− data. Furthermore, the metabolic equivalents (METs) of VO2peak and VO2mean were calculated. To compare different recovery modes, HRpost, ∆HR, VO2post, ∆VO2, recovery La−, and recovery ∆La− were analyzed. Results: HRpeak, VO2peak, and peak La− during HIHY showed no differences between the two groups (p > 0.05). Values of HRpeak, HRmean, METs of VO2peak and VO2mean, and La− during HIHY were 95.6% of HRmax, 88.7% of HRmax, 10.54 ± 1.18, 8.67 ± 0.98 METs, and 8.31 ± 2.18 mmol∙L−1, respectively. WOxi was significantly higher compared to WPCR, WGly, and anaerobic contribution (WPCR + WGly), in kJ and % (p < 0.0001). VO2post and recovery ∆La− were significantly higher in the active recovery group (p < 0.0001, p = 0.0369, respectively). ∆VO2 and recovery La− was significantly lower in the active group compared to the passive group (p = 0.0115, p = 0.0291, respectively). Conclusions: HIHY performed for 10 minutes is a suitable option for relatively healthy people in the modern workplace who may have hatha yoga experience but do not have time to perform prolonged exercise. Following active recovery, they can participate in further HIHY sessions during short breaks. Furthermore, a faster return to work can be supported by physiological recovery.